Geração à Rasca and beyond: Mobilizations in Portugal after 12 March 2011 - Baumgarten, B. (2013)
This article analyses the Portuguese mobilizations that started with the Geração à Rasca in March 2011. The author argues that international events and the import of ideas from movements abroad had an important impact on the organizational structure and the claims of the Portuguese mobilizations. The nation-state, however, remains a very important factor in activism: organizational structures as well as claims are to a great extent country-specific. The article provides also an overview of the protest events and the field of actors involved in the organization of protest. Data come from 10 months of field research, which included participant observations, in-depth interviews and the analysis of websites and mailing-lists.